Syphilis in pregnancy and congenital syphilis notified in a public maternity hospital in Petrópolis – RJ - Veiga, Álvaro José Martins de Oliveira; Oliveira, Giovanna Velloso de; Valentin, Rafael Vincenzo; Barbosa, Adauto Dutra Moraes; Velloso, Luciana Teixeira (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: Syphilis is a disease of high incidence in Brazil and when it occurs during pregnancy, it has important public health implications, as it is responsible for high rates of perinatal fetal mortality and morbidity. Objective: To verify the prevalence of gestational syphilis, the epidemiological profile of the pregnant woman and outcomes such as congenital syphilis. Methods: Descriptive and retrospective study of maternal and newborn data, obtained from the notification forms of SINAN, medical records, and delivery book of the HEAC maternity ward, from January 2017 to December 2019. Results: Four hundred and eighteen pregnant women with syphilis had a pregnancy outcome at HEAC. Seroprevalence for syphilis in pregnant women was 3.95% in 2017, 4.92% in 2018, and 4.73% in 2019. 204 (48.8%) women received adequate treatment before delivery. Among the outcomes, all were reported as congenital syphilis, with 45 (10.7%) having abortions or stillbirths and among live births, 58 (15.54%) were premature and 67 (17.9%) had some manifestation clinic. Conclusion: The number of pregnant women admitted to HEAC who were notified with gestational syphilis was higher than the average notification for these conditions found in Brazil in the years studied, but it was similar to the average found in the State of Rio de Janeiro. Over-reporting of congenital syphilis was identified, and newborns exposed to syphilis were included in this diagnosis, without criteria for congenital syphilis. Our reporting system proved to be fragile and unable to assess the real situation of congenital syphilis in HEAC.